Analysis of the Influence of Tread Pattern on Tire Grip on Road Surface - Witoni Witoni; I Surya; L Vectra (Bandar Lampung University (UBL), 2017)
The role of tires on motor vehicles is very important, and very useful for reducing vibrations caused by road surface. Tires are the components of a vehicle that is in direct contact with the road. When we are driving a vehicle, the tires will also protect the wheel from wear and damage, as well as provide stability between the vehicle and the condition of the road surface to increase speed and facilitate the movement or friction between the tire with the road surface. Tires are one component of a vehicle that has a very vital function, in addition to controlling direction of the vehicle tires also functioned as penaggung vehicle weight including passengers it greatlyaffects the stability and performance of the tire during use so that the required accuracy in the selection of tires for vehicles. The study entitled